Factors Affecting the Consumers' Behavior - Sathana, V. (Bonfring, 2012)
The study of consumer behavior provides valuable information about consumers and prospects, including probable likes and dislikes, spending patterns and motivators to purchase. In a consumer society, the choice of things to consume is vast. Researcher undertakes in-depth research on consumer behavior in order to determine what causes people to buy what they do. The consumer-product interface is the result of an extensive (Fifteen) array of influences. Responses were collected from 300 customers from Jaffna city. Convenient sampling technique was used in selecting the customers. Statistical technique of Factor Analysis was made. In this research, most preferred selection was Signal brand. This research was conducted to study the influencing factors of most selected brand. The present study attained five factors as product factor, personal factor, and competitive factor social factor and Distribution factor. It can be concluded that the consumer toothpaste behavior towards toothpaste will highly depend on the adaptability of all the above mentioned factors.
Keywords: Consumer Behavior; Distribution Factor; Product Factors; Personal Factors; Social Factors